Manejo de la acidez y encalamiento de los suelos - Ortega, J. (United Nations Development Programme, 1985)
Strategies for managing the problem of soil acidity without making massive lime applications are proposed. The 1st strategy consists of the addition of lime to reduce Al saturation, taking into account 3 basic considerations: dose determination, utilization of good quality materials for liming, and estimation of residual effects of lime. The 2nd strategy proposes the addition of lime to supply Ca and Mg and to stimulate its movement in the subsoil, taking into account Ca and Mg availability, fertilizer requirements, and the descending movement of Ca and Mg. The 3rd strategy involves the utilization of bean var. tolerant to Al and Mg through the selection of a great no. of ecotypes whether in culture solutions, in the greenhouse, in the field, or in a combination of the 3. (CIAT)